ESTIMATING FORMWORK STRIKING TIME FOR CONCRETE MIXES (Nigerian Journal of Technology, 2015)
In this study, we estimated the time for strength development in concrete cured up to 56 days. Water-cement ratios adopted range from 0.44-0.57. Nonlinear regression analysis performed on each experimental data set produced Strength-Age (S-A) curves from which Duration-Strength (D-S) models were deduced to estimate approximate time in hours for a particular strength development. A quick reference table for soffit formwork striking time and removal of props was produced. The time to attain the characteristic strengths for C20, C25, C30 and, C35 concrete were 247.04 hours (10.3 days), 285.57 hours (11.90 days), 484.54 hours (20.20 days), 481.58 hours (20.10 days) and, 267.72 hours (11.16 days), 338.74 hours (14.11 days), 560.67 hours (23.36 days), 482.49 hours (20.10 days) for medium and high slump range respectively. Faster construction scheduling operations can be achieved by using lower water-cement ratios and higher grades of concrete.   http://dx.doi.org/10.4314/njt.v35i1.1